Development of thermal energy generator for low power application - Nik Siti Aisyah bt Rokman (Department of Electronic Engineering Technology, Faculty of Engineering Technology, University Malaysia Perlis, 2015)
Development of thermal energy generator for low power application is the product that can generate energy by heat to produce an electrical energy. This project use a peltier as a main part of component. This peltier can generate the electrical directly from heat. The heat production is one possible step towards getting an object moving so that it has kinetic energy. From the results of the kinetic energy will generate the electricity.While, the software that will use for the simulation for the circuit is proteous this is because this software is more functioning and easy to get the component than other software. This project using proteous software to ensure and measure how much heat can be collected when the voltage reaches the maximum level at 12VDC.Heat is the the best energy that can be as a source for generated dc voltage for the renewable energy. The construction of step up voltage regulator circuit is to step up a voltage from 3 VDC to 12 VDC. This project is for develop of 12 VDC portable charger for low power application.In disaster situation like floods situation, the electricity they use is limited or must disconnect the supply from TNB to prevent the short circuit. In this situation they may not have electricity to charge their mobile phone to make emergency call. From the heat from camp fire they can use as a source for generated dc voltage. The small voltage that generated by thermal energy module only 0.5 to 1V so that the step up voltage generator were construct to make the output voltage 12VDC and the voltage can apply to load like mini fan 12VDC or bulb 12VDC.